Analisis Kurs, Inflasi dan Konsumsi Beras Perkapita Terhadap Impor Beras Di Indonesia - Chica Kurniawan; Khairil Anwar; Fanny Nailufar (Fakultas Ekonomi Universitas Samudra, 2021)
This study analyzed the relationship between exchange rates, inflation, andrice consumption per capita on rice imports in Indonesia. The data used inthis study are secondary data during the 2007-2018 period and by 6 mainrice exporting countries. The analysis tool used was the panel data analysismethod (a combination of cross-section and time-series) with the OrdinaryLeast Square (OLS) approach. The results indicated that the relationshipbetween exchange rate and inflation did not affect the level of rice imports inIndonesia because the exchange rate and inflation cannot influenceconsumption and import needs in Indonesia. Meanwhile, per capita riceconsumption also did not have a significant effect on rice imports inIndonesia because there has been a change in consumption patterns at thehead of household level in Indonesia so that the level of rice consumptioncontinues to decline each year.